Analysis of Mosquito Repellent Usage Habits as an Effort to Prevent Malaria Mosquito Bites in FKM UINSU Tuntungan Students - Nanda, Meutia; Masyithah, Ruhul; Siregar, Siti Romaito; BatuBara, Rini Warahmah; Putri, Adelia (PROMOTOR, 2025)
Malaria is a communicable disease that remains a significant public health problem in Indonesia and can be fatal. University students, as a productive age group, play an important role in disease prevention efforts. This study aims to analyze the habits of using mosquito repellent as a preventive measure against malaria mosquito bites among students of the Faculty of Public Health at UINSU Tuntungan. This research employed a quantitative approach with a descriptive design. The sample size of 101 respondents was determined using the Slovin formula from a population of 442 students with a 10% margin of error. Primary data were collected through an online questionnaire. The results showed that 62.4% of students used mosquito repellent, yet 69.3% still experienced mosquito bites within the past week. Most used repellents daily (39.6%) and in the bedroom (82.2%), with spray repellents being the most common choice (45.5%). These findings indicate that although awareness of repellent use is relatively high, consistency in usage and selecting effective products need to be improved to support optimal malaria prevention.